Β-Cyclodextrin catalysed C–C bond formation via C(sp3)–H functionalization of 2-methyl azaarenes with diones in aqueous medium. Issue 2 (18th December 2014) - Kumar, Atul; Dutt Shukla, Ratnakar
Abstract : β-Cyclodextrin catalysed C(sp 3 )–H functionalization of 2-alkyl-azaarenes with homocyclic as well as heterocyclic diones in water has been developed. This biomimetic catalyst oriented methodology provides a sustainable protocol for C–H functionalization, an area mainly dominated by transition metals. Abstract : The first β-cyclodextrin catalysed C(sp 3 )–H functionalization of 2-alkyl-azaarenes with homocyclic as well as heterocyclic diones in water has been developed. This biomimetic catalyst oriented methodology provides a sustainable and green protocol for C–H functionalization, an area mainly dominated by transition metals.